Investigating Wave Transmission through Curtain Wall Breakwaters under Variable Conditions - Vu, Hoang Thai Duong; Zemann, Moritz; Oberle, Peter; Seidel, Frank; Nestmann, Franz (Journal of Coastal and Hydraulic Structures, 2022)
Coastal erosion has become a pressing problem all over the world, especially in areas where the hinterland is only slightly elevated over the sea level. The ongoing progression reveals the urging need for engineered coastal protection measures like breakwaters. Amongst others, curtain wall breakwater types (CWB) have proven their potential to dissipate the wave energy in multiple studies. Their application is often considered in situations where only a partial protection of the coast is needed (e.g. to maintain a hydraulic connectivity or enable sediment transport for land reclamation). Due to their slender design, they are assumed to offer an economical alternative in comparison to massive breakwater constructions, while their pillar-based foundation shows advantages for applications under soft soil conditions. Within the development process of a detached breakwater to face coastal erosion in the Mekong Delta, different types of CWB configurations have been investigated under regular wave conditions. Several characteristics of CWB structures such as the inclination and thickness of the wall, the height of the structures, the rate of submergence and emergence were examined for different water depths and wave parameters. The wave-structure interaction was analyzed using FLOW3D software, which is capable of simulating wave transformation. It showed a high agreement in comparison with own experimental investigations and the wave theory. The results showed a continuous reduction of the wave transmission coefficient with increasing inclination from 90° to 135°, whilst the orientation of the inclination (e.g. 60° vs 120°) only showed a minor effect regarding the wave reduction. All CWB arrangements showed increasing performance with decreasing wave periods. Besides, the wave transmission was mainly impacted by the level of submergence together with the amount of supporting piers and the thickness of the structures. Water depth changes due to tidal influence revealed an increase in wave transmission coefficient once the wave started to overtop the structure.